Sendo médico em português: histórias vividas e narradas por dois médicos cubanos em atuação no Brasil - Silva, Suiane Bezerra da (2023)
In 2016, I had my first opportunity to teach Portuguese lessons abroad to speakers of other languages. My students were Cuban doctors who were preparing for the international mission organized by the Ministries of Health and Education through the "Mais Médicos" Physician Recruitment Program. After the end of the Welcome and Assessment Module (MAAv), i.e., the course that physicians had to attend as a prerequisite for entering the program, I was interested in learning about the life these doctors were going to have in Brazil. Thus, this is a narrative research study, based on the theoretical-methodological perspective of Clandinin and Connelly (2000; 2015), whose overall objective is to gain further insights into the experiences narrated by two Cuban doctors working in Brazil. Particularly, my goals were to: a) analyze and discuss the experiences lived and reported in the narratives of the two doctors working in Brazil when they still had had little contact with Portuguese and b) identify and discuss the strategies the male and female Cuban physicians used for communicating with their patients during medical consultations. My motivation for conducting this study lies in my understanding of language as an important means of communication, interaction, and social inclusion. Thus, knowledge of the stories told by physicians can unveil the relationships and interactions between them, the Brazilian community, and the context of their host country, because to successfully perform their duties, the physicians would have to be able to communicate effectively with their patients. Also, everyday life would require practical resolutions, such as paying bills, going grocery shopping, taking a taxi, etc. Therefore, what the physicians reported on their interactions with Brazilians and their surroundings, on whether their presence was accepted or rejected, and on whether they could provide health care assistance, are strong narrative components that can account for a social and linguistic phenomenon that has manifested itself in our society. While discussing the experiences narrated by the participants, I addressed the following concepts: experience, as developed by educator John Dewey (1979); language variation, according to authors such as Bagno (2002), Calvet (2002), Gnerre (1998); language anxiety, an expression coined by MacIntire and Gardner (1991a, 1991b); personal knowledge, professional knowledge (ELBAZ, 1983; FENSTERMACHER, 1994; CLANDININ AND CONNELLY, 1985; 1988; 1995) and reflective practitioners (SCHÖN, 1983; 1992); primary health care attributes (STARFIELD, 2002), among others that I have considered to be relevant to the points raised. The physicians’ narratives that were selected to compose this study are stories of shared learning and knowledge, of communication strategies, of prejudice, among other meaningful aspects.